Identification of the proteolytically activated form of protein kinase C in stimulated human neutrophils. - Pontremoli, S (1990)
The proteolytically activated form of protein kinase C has been identified in human neutrophils by using a monoclonal antibody that recognizes both the native kinase and the catalytically active proteolytic fragment (protein kinase M). Stimulation with fMet-Leu-Phe results in the conversion of approximately 30% of native protein kinase C to protein kinase M, with little evidence of further degradation. Stimulation with phorbol 12-myristate 13-acetate, on the other hand, causes only a transient formation of protein kinase M, with complete loss of total kinase activity. These differences are related to the differences in biochemical responses, reported earlier, in neutrophils exposed to these two activators.